Identity (Re) construction of International Students When Learning English - Raissa Husna; Nasrullah Nasrullah (Institut Agama Islam Negeri Palopo, 2023)
This qualitative study aims to investigate how English language acquisition and identity building relate from the viewpoint of English language learners. Data for this study was gathered via interviews with international students majoring in English education using narrative studies. Participant’s use of concepts as varied as personal and social traits, ethnic origin, geographic location, religious affiliation, national customs and rituals, and national values, among others, to define the notion of identity was observed. The respondent also thinks that his experience of displacement has a significant impact on how his identity is rebuilt. From the interview, the subjects interviewed considered the impacts above to have positive and negative impacts on international students.